EVALUASI PROGRAM PENDIDIKAN ANTI BULLYING DALAM MENCEGAH PERILAKU BULLYING DI BEBERAPA SEKOLAH MENENGAH PERTAMA (SMP) DI KOTA MAKASSAR - Ismayanti; Kamaruddin, Syamsu A (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to evaluate the effectiveness of anti-bullying education programs in preventing bullying behavior in several junior high schools (SMP) in Makassar City, as well as to identify the factors that influence their success and the challenges faced during implementation. Using a literature review method, this research analyzes journals, policy documents, and previous studies related to anti-bullying programs implemented between 2015 and 2024. The findings show that Makassar’s anti-bullying initiatives such as the Child-Friendly School program, school-based anti-bullying task forces, teacher training, public awareness campaigns, counseling services, and student-led initiatives like Roots Indonesia have contributed significantly to reducing bullying incidents, particularly in schools with strong administrative support, well-trained teachers, active student engagement, and parental involvement. However, program effectiveness remains limited in schools experiencing challenges such as inadequate resources, inconsistent implementation, lack of safe reporting mechanisms, and school cultures that tolerate mild verbal aggression. Overall, the study concludes that program success is strongly influenced by implementation quality and cross-stakeholder collaboration. Therefore, continuous evaluation, enhanced teacher capacity, and strengthened cooperation among schools, parents, and communities are essential to create safe and violence-free learning environments.